REKONSTRUKSI TAFSIR AYAT-AYAT BERPOTENSI TATHARRUF DENGAN PERSPEKTIF ISLAM WASATHIYAH DI ERA PANDEMI - Maliki, Ibnu Akbar; Nasrudin, Muhamad; Mukti, Digdo Aji; Robiansyah, Robiansyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2022)
A solid society based on nationalism is absolutely necessary for the Indonesian nation during the Pandemic. However, in reality there are still internal conflicts due to excessive religious practices (tatharruf) which are based on the verses of the Qur'an. The forms of tatharruf include the existence of a discourse on the basis of the state, acts of intolerance, and narrow interpretations of religious texts. This is certainly an obstacle in efforts to deal with the impact of the pandemic. Surah Al-Baqarah [2]: 143 confirms that the position of Islam is to be in the middle (wasatiyah), not to overdo it and not to underestimate it. This study will examine the reconstruction of verses that have the potential to be taharruf with the Islamic perspective of wasatiyah in the pandemic era. This research is the result of a descriptive qualitative literature review with an inductive approach. The results of the study show that wasatiyah Islam as an interpretive strategy is reflected in 'moderate' theology in the al-Asy'ariyyah doctrine which emphasizes two things, namely: a contextual approach by considering the context of space and time; and pay attention to aspects of benefit. As a tatharruf solution, Islam wasatiyah as an interpretation strategy provides the following views: On the issue of the basic discourse of the state, the caliphate is not a solution that can be applied in viewing the issue of government failure during a pandemic because it is prone to causing conflict in a multicultural society. On the issue of intolerance, Wasatiyah Islam recognizes the right for adherents of other religions to allow them to choose and carry out the guidance of their respective religions. Then on the issue of narrow religious interpretations about Covid-19, it is important for us to anticipate fear by considering the benefit, as stated in the MUI Fatwa.